CD 59 Targeted Ultrasensitive Electrochemical Immunosensor for Fast and Noninvasive Diagnosis of Oral Cancer. Issue 10 (6th October 2016) - Choudhary, Meenakshi; Yadav, Prashant; Singh, Anu; Kaur, Satbir; Ramirez‐Vick, Jaime; Chandra, Pranjal; Arora, Kavita; Singh, Surinder P.
Abstract: Oral cancer (OC) is one of the important cancer types in human being and its early and quick diagnosis will help clinicians to develop suitable therapeutic strategies to improve the prognosis of cancer patients. In this direction, we report a label free impedimetric immunosensor to diagnose OC by detecting CD 59, an early stage and important OC biomarker. The immunosensor probe is fabricated by immobilizing CD 59 antibodies (anti‐CD 59) on a self‐assembled molecular layer of L‐cysteine (Cys) on a gold electrode. The fabrication of sensor probe is characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The experimental conditions were optimized in terms of antibody concentration, temperature, pH, and incubation time in order to obtain maximum sensitivity. The CD 59 is qualitatively detected using EIS which shows a wide dynamic range between 1 fg mL −1 and 1000 fg mL −1 with a detection limit of 0.38 (±0.03) fg mL −1 . The developed immunosensor is successfully applied for direct detection of CD 59 in clinically relevant human saliva samples. Interferences due to non‐target cancer antigens, stability, and regeneration of the developed immunosensor was performed. Abstract :